How to measure mental illness stigma at work: development and validation of the workplace mental illness stigma scale - Matousian, Naseli; Otto, Kathleen (Frontiers in Psychiatry, 2023)
The study objective was to design a new theoretically driven multidimensional scale for the use in the empirical measurement of stigmatizing attitudes towards persons with mental illness within the return-to-work process as this integral part of vocational reintegration has been widely neglected by scholars so far. Therefore, we developed and validated a 21-item instrument to comprehensively measure the three-factorial structure of stigmatizing attitudes (affect, cognition, behavior) across two studies (overall N = 251). In both studies the new scale proved to be highly internally consistent, and its proposed three-factor structure was equally supported across the two studies. Convergent and discriminant validity were demonstrated by moderate and high correlations or zero correlations with pertinent measures. Furthermore, construct validity of the new scale was supported by significant positive associations with relevant personality characteristics within stigma research. The WMISS is the first instrument to measure mental health stigma specifically within the return-to-workprocess and demonstrates strong psychometric properties. Inclusion of this scale in future research can help facilitate understanding of mental illness stigma within the occupational sector and assist with targeted intervention development.